2018
DOI: 10.1177/1758573218755569
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the minimum data sets for primary shoulder arthroplasty between national shoulder arthroplasty registries. Is international harmonization feasible?

Abstract: The aims of this study were to identify the common components of the Minimum Data Set (MDS) of current national shoulder arthroplasty registries that could be pooled for analysis; and to determine whether further harmonisation of data collection across these registries would be feasible. Copies of primary shoulder arthroplasty MDS forms, annual reports, and other publications from national shoulder arthroplasty registries were identified using internet search engines up to November 2016. Data relating to local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…None of the nine national joint registries which include outcomes for shoulder arthroplasty currently report on patient reported outcomes or survivorship of revision implants. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the nine national joint registries which include outcomes for shoulder arthroplasty currently report on patient reported outcomes or survivorship of revision implants. 27 …”
Section: Resultsmentioning
confidence: 99%
“…The data for hemiarthroplasty is taken from Sassoon et al 22 The data for TSA at 1 year is reported by Bartels et al, and 10 year data were extracted from Aibinder et al 12,13 None of the nine national joint registries which include outcomes for shoulder arthroplasty currently report on patient reported outcomes or survivorship of revision implants. 27…”
Section: Survivorshipmentioning
confidence: 99%
“…Of the nine national joint registries reporting outcomes in shoulder arthroplasty, only the Australian registry contains survivorship outcomes stratified by age, implant type and implant indication. 8 , 34 A further article reported on outcomes from the Danish Joint Registry, however these data were not included in the meta-analysis due to an absence of confidence intervals. 29 Survivorship was reported separately for several different age groups and implant types in the Australian National Joint Registry.…”
Section: Resultsmentioning
confidence: 99%
“…Nine national joint registries report on shoulder replacements, annual reports were reviewed for outcome data stratified by age. 8 …”
Section: Methodsmentioning
confidence: 99%
“…Ein wichtiger Schritt ist hier die Aufnahme der Standzeiten und Erfassung der klinischen Ergebnisse der Revisionsprothetik in den Prothesenregistern. Keines der neun nationalen Prothesenregister mit ihren Ergebnissen und Standzeiten für die Primärprothetik, erfasst im Moment das Outcome in der Revisionsendoprothetik [ 3 ]. Des Weiteren sollte man die Unterschiede zwischen Nordamerika und Europa in Betracht ziehen.…”
Section: Ergebnisse Der Revisionsendoprothetikunclassified